TEACHER'S QUESTIONING STRATEGIES IN CLASSROOM INTERACTION - Hadiani, Siti Nur (2014)
This study investigates the questioning strategies employed in classroom interaction in one public senior high school in Cimahi. This study, thus, intends to explore what questioning strategies are applied by the teacher in the classroom interaction along with teacher's and students' perceptions of the questioning strategies applied in the classroom interaction. To meet the purposes of the study, a case study was employed. The data were obtained from classroom observation, interview with the teacher and interview with students. The basic frameworks of questioning strategies analysis are relied on Chaudron (1988), Wu (1993), Anwar (2000) and Tsui et al (2004) frameworks. This study revealed that the teacher employed several questioning strategies namely rephrasing, blank-filling, code-switching, probing, simplification, exemplification, repetition, and decomposition in eliciting the students' responses. However, the most dominant questioning strategy employed by the teacher was rephrasing strategy since this strategy was effective in eliciting the students' responses in the classroom interaction. This result was supported by the result of the interview with the students which revealed that the most helpful questioning strategy for the students was rephrasing strategy. The teacher and the students generally gave positive perceptions toward questioning startegies. For the teacher, questioning startegy is one of the teacher's tools in eliciting students' responses. Meanwhile, for the students, questioning strategies are really helpful in comprehending the teacher's questions and also helpful in gaining confidence to express their ideas verbally. Based on the findings, it is recommended that future research concerning the implementation of questioning strategy in Indonesia should be enriched with more attention to the correlation between the implementation of questioning strategies and students' achievement. Keywords: Teacher's Questioning Strategies, Classroom Interaction. Penelitian ini meneliti strategi bertanya yang digunakan guru dalam interaksi kelas di sebuah SMA negeri di Cimahi. Maka dari itu, penelitian ini bertujuan untuk menelaah strategi bertanya apa yang digunakan oleh guru dalam interaksi kelas beserta persepsi guru dan siswa mengenai penggunaan strategi bertanya tersebut dalam interaksi kelas. Dengan mempertimbangkan tujuan dari penelitian ini, studi kasus dipilih sebagai metode yang cocok untuk digunakan. Data yang dibutuhkan dikumpulkan dari beberapa instrumen yang digunakan, yakni observasi kelas, wawancara dengan guru dan wawancara dengan siswa. Kerangka kerja dasar yang digunakan dalam menganalisis strategi bertanya dikembangkan berdasarkan kerangka kerja dari Chaudron (1988), Wu (1993), Anwar (2000) dan Tsui et al (2004). Berdasarkan hasil temuan, rephrasing, blank-filling, code-switching, probing, simplification, exemplification, repetition, dan decomposition adalah jenis strategi bertanya yang sering digunakan oleh guru dalam usaha memperoleh respon siswa. Meskipun demikian, strategi bertanya yang paling dominan digunakan oleh guru dalam interaksi kelas adalah strategi rephrasing karena, berdasarkan hasil analisis, strategi ini efektif dalam mendorong siswa untuk memberikan respon. Hasil analisis ini juga didukung oleh hasil wawancara dengan siswa yang mengungkapkan bahwa strategi bertanya yang sangat membantu siswa dalam memahami pertanyaan guru adalah strategi rephrasing. Secara umum, guru dan para siswa memberikan persepsi positif terhadap penggunaan strategi bertanya. Bagi guru, strategi bertanya merupakan salah satu cara guru dalam memperoleh respon dari siswa. Sedangkan bagi para siswa, strategi bertanya sangatlah membantu mereka dalam memahami pertanyaan yang diberikan oleh guru dan juga sangat membantu siswa dalam menumbuhkan kepercayaan diri untuk mengemukakan pendapat maupun ide mereka secara verbal. Berdasarkan hasil temuan, direkomendasikan untuk penelitian selanjutnya untuk lebih memfokuskan penelitian terhadap korelasi antara pengimplementasian strategi bertanya dan pencapaian siswa. Kata kunci: Strategi bertanya guru, Interaksi kelas